Social Media – A Vehicle for Personalisation in Politics? Political communication before the 2017 parliamentary elections in Iceland - Birgir Guðmundsson; Baldur Sverrisson (The University of Akureyri, 2019)
This paper focuses on political communication prior to the 2017 parliamentary elections in Iceland. By means of content analysis and interviews with party officials the extent of central party control and the extent to which social media are a vehicle for personalisation are explored. The findings suggest a relatively low level of central party control and that social media, in particular Facebook is indeed a vehicle for personalisation. The analysis furthermore shows a difference in the social media use of plain candidates and party leaders, parties, and regions/constituencies. Finally, Facebook is more of a tool for personalization while Twitter is a more political platform.